Small business opportunities are there for the taking - Nago, Mathurin Coffi (Technical Centre for Agricultural and Rural Cooperation, 1996)
Mathurin Coffi Nago is a specialist in food processing. He is Professor of Biochemistry and Food Technology at the Faculty of Agricultural Sciences, the National University of Benin and Coordinator of the Regional Applied Nutrition and Food Centre...